Effect of attitudes towards traffic safety and risk perceptions on pedestrian behaviours in Vietnam - D.D. Dinh; N.H. Vũ; R.C. McIlroy; K.A. Plant; N.A. Stanton (IATSS Research, 2020)
This study explores the relationships between attitudes towards traffic safety, risk perceptions and pedestrian behaviours in Vietnam. A questionnaire survey was conducted with a sample of 835 Vietnamese road users. The results from regression analyses and a structural equation model showed that safer attitudes towards traffic safety and higher levels of traffic risk perception are associated with safer pedestrian behaviours. In addition, traffic safety attitudes were found to partially mediate the association between traffic risk perception and pedestrian behaviour. Furthermore, traffic risk perception was significantly predicted by non-traffic risk perception, and people who had higher level of risk perceptions of both kinds were also prone to report safer attitudes towards traffic safety. The practical implications for traffic safety interventions in Vietnam are also discussed.